Double parton interactions in gamma+3 jet events in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Calfayan, P.; et al. (Amer Physical Soc, 2010)
We have used a sample of gamma + 3 jets events collected by the D0 experiment with an integrated luminosity of about 1 fb(-1) to determine the fraction of events with double parton scattering (f(DP)) in a single p (p) over bar collision at root s = 1.96 TeV. The DP fraction and effective cross section (sigma(eff)), a process-independent scale parameter related to the parton density inside the nucleon, are measured in three intervals of the second (ordered in p(T)) jet transverse momentum p(T)(jet2) within the range 15 <= p(T)(jet2) <= 30 GeV. In this range, f(DP) varies between 0.23 <= f(DP) <= 0.47, while sigma(eff) has the average value sigma(ave)(eff) = 16.4 +/- 0.3(stat) +/- 2.3(syst) mb.